Teacher Innovation in Elementary School Education: Improving the Quality of Learning in the Digital Era - Susilawati, Samsul; Yaqin, Mohamad Zubad Nurul; Chakim, Abdullo; Putri, Candra Avista; Pepridel, Nurul Izhan Yolanda (Proceeding of International Conference on Islamic Education (ICIED), 2024)
In the increasingly advanced digital era, the need for innovation in the world of education is increasing. It is increasingly urgent, especially in the context of elementary school teacher education. The purpose of this study aims to explore in the education of elementary school teachers based on digital technology and its impact on the quality of education. The method in this study uses a descriptive qualitative approach. This research was conducted at MI Al-Lathifiyah by involving teachers who have applied digital technology in the learning process. Data were collected through in-depth interviews, participatory observations, and documentation analysis. The results of the study show that the application of digital technology can increase student activity, teaching creativity, and teachers' digital use competence. Nonetheless, challenges such as infrastructure limitations and technology access gaps have also been identified. These findings underscore the importance of ongoing support for teachers and development in technology infrastructure to maximize digital innovation in education.